IN HOUSE TRAINING (IHT) MODEL TO IMPROVE THE ABILITIES OF ENGLISH TEACHERS IN DEVELOPING TEACHING MATERIALS - Lengkanawati, Nenden Sri; Setyarini, Sri; Sari, R. Della Kartika; Moecharam, Nicke Yunita (Indonesian Journal of Applied Linguistics, 2015)
The Ministerial Regulation Number 16 of the year 2007 on academic qualification standards and teacher competencies requires teachers to demonstrate four competencies: personality, social, pedagogical, and professional. However, there are two competencies (pedagogical and professional) which become the stumbling obstacles for teachers of English in their professional involvement. Therefore, this study was designed to aim at: (1) creating a conceptual framework for enhancing teachers’ capabilities in developing and implementing teaching materials; (2) designing a model of IHT to improve the ability of teachers to develop and implement the use of teaching materials; and (3) piloting and implementing the IHT model in teacher training programs. The method used in the data analysis adopted a qualitative design with reference especially to the theory of the development of teaching materials (Crowford: 2002) and the design of IHT (Wallace: 1993). The results showed that most respondents tended to resort to the textbook as the primary source for students’ learning activities, with some enrichment materials obtained from the Internet and other sources. Nevertheless most of the teachers were still found to encounter quite a few obstacles in developing their teaching-learning materials, appropriate to the topics as indicated in the syllabus and to the student characteristics. To alleviate this hurdle, the IHT model to be incorporated in a teacher training program could be an effective alternative to improve the ability of the teachers in developing their English teaching-learning materials.